An Investigation of the Scale and Spread of Child Marriage in the Suburbs of Mashhad (Ismaeel-Abad Region), Focused on Causes, Factors, and Preventive Solutions - Tamizi, Mahboobeh (2021)
The phenomenon of Child Marriage is referred to as a marriage or similar union between a child and an adult or another child under the age of eighteen. The causes of child marriage include: family relations, sexual discrimination, controlling sexual relationships and maintaining the dignity of the family, certain economic factors and other social and cultural factors as well. Among the effects of early marriage on children it can be pointed to divorce at young ages and its risks for girls, dropout, harming of children’s sexual health and their fertilization rights an instance of which is early pregnancy putting both the mother’s and infant’s health at risk, sexual dissatisfaction, increased violence and exploitation, violation of child rights, and lack of ability to manage life affairs. Filed investigations on the factors of child marriage in the Ismaeel-Abad district of Mashhad show that the most important factors that promote child marriage in the investigated area include economic factors and social attitudes. In terms of solutions aimed at mitigating the rate of child marriage, fighting poverty, training families and promoting their awareness, empowering the youth, reviewing and amending the laws, and correcting the cultural procedures of selecting a spouse can be considered to be potentially effective.